ALPPS Versus Portal Vein Embolization for Hepatitis-related Hepatocellular Carcinoma: A Changing Paradigm in Modulation of Future Liver Remnant Before Major Hepatectomy. Issue 5 (May 2021) - Chan, Albert; Zhang, Wei Yi; Chok, Kenneth; Dai, Jeff; Ji, Ren; Kwan, Crystal; Man, Nancy; Poon, Ronnie; Lo, Chung Mau
Abstract : Objective: The aim of this study was to evaluate the short- and long-term outcome of associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) for hepatitis-related hepatocellular carcinoma (HCC). Summary Background Data: ALPPS has been advocated for future liver remnant (FLR) augmentation in liver metastasis or noncirrhotic liver tumors in recent years. Data on the effect of ALPPS in chronic hepatitis or cirrhosis-related HCC remained scarce. Methods: Data for clinicopathological details, portal hemodynamics, and oncological outcome were reviewed for ALPPS and compared with portal vein embolization (PVE). Tumor immunohistochemistry for PD-1, VEGF, and AFP was evaluated in ALPPS and compared with PVE and upfront hepatectomy (UH). Results: From 2002 to 2018, 148 patients with HCC (hepatitis B: n = 136, 92.0%) underwent FLR modulation (ALPPS, n = 46; PVE: n = 102). One patient with ALPPS and 33 patients with PVE failed to proceed to resection (resection rate: 97.8% vs 67.7%, P < 0.001). Among those who had resections, 65 patients (56.5%) had cirrhosis. ALPPS induced absolute FLR volume increment by 48.8%, or FLR estimated total liver volume ratio by 12.8% over 6 days. No difference in morbidity (20.7% vs 30.4%, P = 0.159) and mortality (6.5% vs 5.8%, P = 1.000) with PVE was observed. Chronic hepatitis and intraoperative indocyanine green clearance rate ⩽39.5% favored adequate FLR hypertrophy in ALPPS. Five-year overall survival for ALPPS and PVE was 46.8% and 64.1% ( P = 0.234). Tumor immunohistochemical staining showed no difference in expression of PD-1, V-EGF, and AFP between ALPPS, PVE, and UH. Conclusions: ALPPS conferred a higher resection rate in hepatitis-related HCC with comparable short- and long-term oncological outcome with PVE. Abstract : Supplemental Digital Content is available in the text